Analisis Dan Perancangan Prototype Sistem Informasi Sekolah Berbasis Website Pada SMPN SATAP 9 Tanjung Jabung Timur - Wiranti; Zaenal Abidin, Dodo; Nurhadi, Nurhadi (LPPM STIKOM Dinamika Bangsa, 2025)
ABSTRACT School website information systems are very important in improving the efficiency of school management, facilitating access to information for students, parents, staff and expanding the scope of school information. Problems at SMPN Satap 9 Tanjung Jabung Timur Village where in terms of the development of school information technology is still difficult to access and not many people know such as school activities, student achievements, student registration info and other important announcements. communication between schools, students, parents and the general public is also hampered, for example to get school information student guardians or interested people must come to the school directly this is less efficient and takes quite a long time. The purpose of this research is to analyze website information management and design a prototype of the school website information system at SMPN Satap 9 Tanjung Jabung Timur Village. the method used is the prototype method with system modeling designed using a unified modeling language, namely use case diagrams, class diagrams and activity diagrams. the results showed that information about SMPN Satap 9 Tanjung Jabung Timur Village is still not widely known by the public so it is necessary to create a website in disseminating information to the wider community. Keywords:Analysis, Design, Information System, Prototype, School Website.